A kind of complex-based electrocatalytic sensor for monitoring the reduction of Cr(Ⅵ) by organic/inorganic reductants. (1st September 2022) - Tang, Shuang; Gao, Yue; Han, Shengwei; Chi, Jie; Zhang, Zhong; Liu, Guocheng
Graphical abstract: Metal-induced 2D→3D coordination polymers act as electrochemical sensors for monitoring the reduction of Cr(Ⅵ) by organic/inorganic reductants (AA, H2 O2 and Na2 S2 O3 ). Abstract: In order to monitor the reduction of Cr(Ⅵ) by organic/inorganic reductants, three transition metal ions of Co 2+ /Ni 2+ /Cu 2+ were selected to combine with a semi-rigid amide ligand [N, N'-bis-pyridin-3-ylmethyl-terephthalamide (L)]. As a result, [Co(L)(HIPA)](H2 O)2 ]∙H2 O (1 ) [Ni(L)(HIPA)](H2 O)2 ]∙H2 O (2 ) [Cu(L)(HIPA)]∙4H2 O (3 ) were obtained by hydrothermal method (H2 HIPA = 5-Hydroxyisophthalic acid). Complexes 1 and 2 are similar 2D cellular networks, while complex 3 has 4-connected 3D structure with semicircle 1D channel. The title complexes can act as electrochemical sensors to detect Cr(Ⅵ) by cyclic voltammetry and differential pulse method. The corresponding detection limits are 5.9 × 10 −6 (1 ), 1.6 × 10 −5 (2 ), 9.1 × 10 −6 (3 ) for Cr(Ⅵ) anion, respectively. In addition, the title complexes 1 –3 modified carbon paste electrode (1 –3 -CPEs) provide a kind of generalizable sensor for the electrochemical monitor the reduction of Cr(Ⅵ) by organic/inorganic reductants [Ascorbic acid (AA), H2 O2 and Na2 S2 O3 ]. The effect of metal ions on the structures and electrochemical properties of 1 –3 were discussed.